Peran Bank Sentral Dalam Menjaga Stabilitas Nilai Tukar: Analisis Kebijakan Moneter di Indonesia - Niswan, Amirsan; Lewa, Muhammad Juwantho (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Exchange rate stability is one of the key indicators in maintaining macroeconomic stability. The central bank plays a strategic role in controlling exchange rate fluctuations through the implementation of appropriate monetary policies. This study aims to analyze the role of Bank Indonesia in maintaining the stability of the rupiah exchange rate through various monetary policy instruments. A quantitative approach is employed using secondary time-series data, including policy interest rates, money supply, inflation, and exchange rates. Data analysis is conducted using regression methods to examine the impact of monetary policy on exchange rate stability. The results indicate that monetary policy instruments have a significant effect on exchange rate movements. These findings suggest that effective monetary policy contributes to exchange rate stability and supports overall economic stability. This study is expected to provide useful insights for policymakers in formulating sustainable monetary policies.